2002
DOI: 10.1080/00221320209598675
|View full text |Cite
|
Sign up to set email alerts
|

Chinese and Dutch Parents' Perceptions of Their Children's Personality

Abstract: The authors coded Chinese (n = 401) and Dutch (n = 324) parents' free descriptions of their 3- to 14-year-old children's personalities using a 14-category coding system partially based on the Big Five. Of the Chinese and Dutch personality descriptors, 86% and 77%, respectively, could be classified in the first 5 main categories resembling the five-factor model of adult personality. No significant differences were found for gender, socio-economic status, or city in these categories. Chinese parents of school ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…In view of the inevitable exposure to different cultural values and life realities in the new environments, researchers believe it is not surprising that Chinese immigrant families change their beliefs and practices. Zhang et al (2002) give evidence that Chinese people everywhere possess some common traits that are grounded in the Chinese culture but develop some additional attributes nurtured by their respective new environments. Lin and Fu (1990), in comparing the child-rearing beliefs and practices among Chinese and immigrant Chinese in the US, also observed the adaptability of the Chinese immigrants to US conditions of life and social structures.…”
Section: Cultural Change Of Immigrant Chinese Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the inevitable exposure to different cultural values and life realities in the new environments, researchers believe it is not surprising that Chinese immigrant families change their beliefs and practices. Zhang et al (2002) give evidence that Chinese people everywhere possess some common traits that are grounded in the Chinese culture but develop some additional attributes nurtured by their respective new environments. Lin and Fu (1990), in comparing the child-rearing beliefs and practices among Chinese and immigrant Chinese in the US, also observed the adaptability of the Chinese immigrants to US conditions of life and social structures.…”
Section: Cultural Change Of Immigrant Chinese Familiesmentioning
confidence: 99%
“…Recent studies show that Chinese parents retain many traditional aspects of parenting values and practices, even when living in a place not of their origin (Chen, 2001;Huntsinger et al, 2000;Lin & Fu, 1990;Zhang, Kohnstamm, Slotboom, Elphick & Cheung, 2002). In a study conducted among American, Chinese-American and Chinese families, comparing parents' attitudes and expectations regarding science education, Chen concluded that 'no significant differences were found between the Chinese and Chinese-American groups ' (2001, p. 310).…”
Section: Traditional Chinese Cultural Orientation Of Child-rearingmentioning
confidence: 99%
“…Zhang, Kohnstamm, Slotboom, Elphick, & Cheung (2002) observed that Chinese in mainland China, Hong Kong, Taiwan, and the US possessed some common traits that are deeply rooted in the Chinese culture and characterized by Confucian thought, such as self-discipline and moderation. On the other hand, even when they are from distinct ethnic religious, regional and experiential groups, acculturated individuals within a nation, as a whole, are, in some ways, more like one another than like individuals from the nation of their foreign heritage (Hofstede, 1980, Table 1).…”
Section: National Culturesmentioning
confidence: 99%
“…Readily accessible country-comparative data on these and many other work-related issues however is lacking. Zhang, Kohnstamm, Slotboom, Elphick and Cheung (2002) compared free descriptions of children by parents and found Chinese parents of school-age children generated many more descriptors, mostly critical, in the domain of conscientiousness. They suggest that these fi ndings refl ect the Chinese high achievement orientation and show that classifi cation (for trait descriptions) is sensitive to cultural diff erences.…”
Section: National Personality Profi Lesmentioning
confidence: 99%